Pedological characterization of two slopes in the Gurutuba River basin, in Itaóca, SP - Cabral, Douglas da Silva; Ladeira, Francisco Sérgio Bernardes [UNESP] (Revista Brasileira de Geografia Fisica, 2024)
The main cause of natural disasters in Brazil is gravitational mass movements and among these, landslides stand out. In this context, the geomorphological region called Serra do Mar, between the states of Paraná and Rio de Janeiro, is daily affected by natural disasters and, mainly, landslides. Thus, this work seeks to characterize pedologically different slopes and determine factors that may influence the occurrence of landslides in a non-uniform manner between the slopes. For this, the study was based on the characterization of soils through tactile-visual field analysis and geotechnical characterization tests in the municipality of Itaóca, SP, in the region known as Vale do Ribeira and inserted in the domain of Serra do Mar. The region was selected due to its geomorphology with steep slopes and which registered numerous planar landslides in the rainy event that occurred in January 2014, when torrential rains in the basins of the Guarda-Mão and Gurutuba rivers, triggered a large number of landslides, causing debris flows and taking approximately 25 lives in the municipality. Thus, it is believed to be possible to analyze the characteristics of different soils on nearby slopes that were equally affected by the rains, but registered an unequal number of landslides.
Caracterização pedológica de duas vertentes na bacia do Rio Gurutuba, em Itaóca, SP
Keywords: Landslides; Pedology; Soils; Susceptibility